2020
DOI: 10.3390/ijerph17082657
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Association between Sleep Duration, C-Reactive Protein, and Uric Acid in Korean Women

Abstract: Serum high-sensitivity C-reactive protein (hsCRP) and serum uric acid (SUA) are biomarkers that predict chronic inflammation and cardiovascular dysfunction. Therefore, we aimed to investigate the association between sleep duration, hsCRP, and SUA in Korean women. Cross-sectional data from the Seventh Korea National Health and Nutrition Examination Survey was analyzed. The odds ratio (OR) and 95% confidence intervals (CIs) for an association between higher hsCRP (>2.0 mg/L) or higher SUA (>5.6 mg/dL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…This study provides further evidence that sleep duration is independently associated with hyperuricemia after adjusting for known risk factors and potential confounders. Unlike a U-shaped curve reported in Korean women [22], our findings indicated that longer sleep (>8 h) could also reduce the incidence of hyperuricemia significantly, which was consistent with previous studies [23,32]. In this prospective longitudinal study, sufficient samples and prospective study design avoided reverse causality by chronological order.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study provides further evidence that sleep duration is independently associated with hyperuricemia after adjusting for known risk factors and potential confounders. Unlike a U-shaped curve reported in Korean women [22], our findings indicated that longer sleep (>8 h) could also reduce the incidence of hyperuricemia significantly, which was consistent with previous studies [23,32]. In this prospective longitudinal study, sufficient samples and prospective study design avoided reverse causality by chronological order.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, only 36.16% of participants had a recommended sleep duration, and over one-half of participants slept less than 7 h. Our results are in line with several previous studies that estimated the association of sleep duration with hyperuricemia. Consistent with previous cross-sectional studies [22,23,31], short sleep duration was considered as a risk factor for hyperuricemia in this study. Appropriate public health actions should be taken to increase the sleep time of the population to reduce the damage to health caused by sleep that is too short, especially among subgroups with a low HDL-C, a high TG, or those who are not overweight.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…First, a major explanation is inflammation, a key factor strongly associated with depression [ 33 ]. Studies have reported both short and long sleep durations and poor sleep quality to be associated with increased inflammatory cytokines such as CRP and IL6 [ 34 36 ]. Second, good sleep quality could help increase levels of melatonin [ 37 ], a pleiotropic regulator molecule that has been reported to alleviate depressive symptoms [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as standard MR is based on the assumption of linearity (24), it would overlook non-linear effects (25). Given that a U-shaped observational association between sleep duration and hyperuricemia was reported in a previous study (18), it is a key research priority to explore the potential non-linear causal relationship between sleep duration and hyperuricemia.…”
Section: Introductionmentioning
confidence: 93%